Comparativo de rendimiento de 10 híbridos simples de Maíz amarillo duro (Zea mays L.) Bajo riego en el distrito de Juan Guerra-San Martin - Bautista García, Miguel Angel (2000)
In order to evaluate the performance of 10 simple hybrid, plus 2 yellow corn witnesses under irrigation of different treatments. a trial randomized complete block at the experimental station "El Porvenir '', located at Km 14.5 of the Marginal Highway South (Tarapoto -Juanjui). Juan Guerra District, San Martin Province and Region (PERU) was performed. geographically located by the coor-ordinates following: West Longitude 76 ° 5 'south latitude 06º 35' and alti-tude of 356 m The standard density planting for treatments under study was 62 500 plants / hectare. high quality seed genetics pro-desirable Germplasm Bank Maize Research Program of the Experimental Station "El Porvenir '' was used. The soil is characterized by a clay loam texture, with a high percentage of organic matter (3.22%). The dose of fertilizer applied was 120-80-60 (N.P.K.), applying nitrogen dose into two fractions. The results show that treatment T9 (PIMLE 72 x PIMLE 7), had the highest grain yield of 5,897 kg / ha re-toting an economic profitability of 1,295.91 Nuevos Soles and a cost benefit ratio of 1.90 Nuevos Soles. Treatment T10 (72 x PIMLE PIMLE 58) record the lowest yield with 3.266 kg / ha.